Nanofacet-density scaling on zig-zag carbon nanotubes within the kinetic 5-vertex growth model - HONTINFINDE, Senan Ida Valerie; KPLE, JOËL; OKE, Djidjoho Toussaint; ZOUNMENOU, Franck; ADDA, Josaphat; HONTINFINDE, FÉLIX (My University, 2022)
Nanofacets density at the edge of a growing zig-zag single-walled carbon nanotube is investigated by means of a kinetic 5-vertex model. The model comprises, carbon atoms deposition and diffusion events that are assumed Markov processes. The nanotube synthesis temperature, the carbon atomic flux from the catalyst nanoparticles, and the diffusion length are the model physical parameters considered. The kinetic equation describing the nanotube growth is solved by Kinetic Monte Carlo simulations and the average nanofacet density at the nanotube edge is calculated. It is found that this quantity displays interesting behaviors, in particular a power-law behavior with the diffusion length and the growth time.
Keywords: Single-walled carbon nanotube; kinetic 5-vertex model; carbon atoms deposition and diffusion; Markov processes; Kinetic Monte Carlo simulations; nanofacet density; power-law behavior; diffusion length; growth time